Construção coletiva de regras e resolução de conflitos: contribuições para o enfrentamento da violência entre alunos - Fernandes, Eliane Pinheiro (2017)
The present study deals with the problem of violence in schools, specifically those related to episodes of physical and verbal aggression among students. The objective was to investigate, through empirical research, whether actions such as the collective construction of rules and resolution of conflicts contribute in reducing the episodes of violence among students, improving the quality of relationships within the classroom. Conflict resolution initially occurred through teacher mediation, and students were gradually encouraged to solve their own conflicts through dialogue. Three teachers from the municipal board of education of the city of São Paulo participated in this research: they worked in the eastern part of it, in different schools of three suburban neighborhoods. In order achieve the goal of the study, participants would have to change their teaching practice, build rules with their students and mediate their conflicts, since if not solved, they can engender violence. The change in pedagogical practice was guided by the Piagetian theory on moral development. The participants were involved in two training sessions in their respective schools, with the consent of their principals. In these sessions, it was presented and discussed: the conceptions of anomie, heteronomy and autonomy, the role of teachers in the moral education of students as well as the relationship between those ideas and violence. To follow up the training process, the teachers could rely on the researcher to listen to their doubts, discuss possibilities of action, orientate the process of collective construction of rules and mediation of conflicts, as well as to suggest study material, whenever necessary. The data were collected through: (a) audio and text messages, sent by the teachers through cell phones, telling about their doubts and narrating episodes related to the rules’ elaboration and conflicts solving among students; (b) semi-structured interviews. For the analysis, these materials were transcript and organized into six categories, which were interpreted according to the theoretical framework adopted, in a qualitative approach. The results indicated that the collective construction of rules and the resolution of conflicts contribute towards the reduction and prevention of violence among students